Cover Feature: MicroRNA Detection by DNA‐Mediated Liposome Fusion (ChemBioChem 5/2018). (16th February 2018) - Jumeaux, Coline; Wahlsten, Olov; Block, Stephan; Kim, Eunjung; Chandrawati, Rona; Howes, Philip D.; Höök, Fredrik; Stevens, Molly M.
Abstract : The cover feature picture shows the fusion of fluorophore‐containing liposomes, driven by the self‐assembly of complementary DNA strands. Here, the DNA complexes are designed to respond to the presence of a specific microRNA sequence. In the presence of the target microRNA, the hairpin DNA (orange) is displaced to reveal a sticky end in double‐stranded DNA, which initiates liposome fusion. Fusion events are detected by an emission of light upon excitation of the donor fluorophore with a laser, symbolized by the red carpet. More information can be found in the communication by F. Höök, M. M. Stevens, et al. onpage 434 in Issue 5, 2018 (DOI:10.1002/cbic.201700592 ). Cover image created by Miguel Spuch Calvar.